Engineering NK-CAR.19 cells with the IL-15/IL-15Rα complex improved proliferation and anti-tumor effect in vivo - Silvestre, Renata Nacasaki; Eitler, Jiri; de Azevedo, Julia Teixeira Cottas; Tirapelle, Mariane Cariati; Fantacini, Daianne Maciely Carvalho; de Souza, Lucas Eduardo Botelho; Swiech, Kamilla; Covas, Dimas Tadeu; Calado, Rodrigo T.; Montero, Paola Ortiz; Malmegrim, Kelen Cristina Ribeiro; Figueiredo, Marxa L.; et al. (Frontiers in Immunology, 2023)
Natural killer 92 (NK-92) cells are an attractive therapeutic approach as alternative chimeric antigen receptor (CAR) carriers, different from T cells, once they can be used in the allogeneic setting. The modest in vivo outcomes observed with NK-92 cells continue to present hurdles in successfully translating NK-92 cell therapies into clinical applications. Adoptive transfer of CAR-NK-92 cells holds out the promise of therapeutic benefit at a lower rate of adverse events due to the absence of GvHD and cytokine release syndrome. However, it has not achieved breakthrough clinical results yet, and further improvement of CAR-NK-92 cells is necessary. In our study, we demonstrated that a fourthgeneration CD19-targeted CAR (CAR.19) co-expressing IL-15 linked to its receptor IL-15/IL-15Rα (CAR.19-IL-15/IL-15Rα) significantly enhanced NK-92 cell proliferation, proinflammatory cytokine secretion, and cytotoxic activity against B-cell cancer cell lines in vitro and in a xenograft mouse model. Together with the results of the systematic analysis of the transcriptome of activated NK-92 CAR variants, this supports the notion that IL-15/IL-15Rα comprising fourth-generation CARs may overcome the limitations of NK-92 cell-based targeted tumor therapies in vivo by providing the necessary growth and activation signals.